TRANSFORMASI IDENTITAS KOTA BITUNG DITINJAU DARI CITRA PARIWISATA HEKSAGONAL ANHOLT - Jouns Candy Felice Lang; Rustono Farady Marta; Alfred Pieter Menayang (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2020)
Building a city branding means building the city's identity. City branding as a strategy is closely related to the city's identity as it is one of the efforts to communicate the identity of the city and give the difference or unique value for the city. Bitung is known for its identity in the fisheries sector and relies on this sector as a main sector of running the city economy, transhipment and moratorium restrictions, the fishery industry in Bitung becomes a slumped down. Identity as the city of Cakalang is not strong enough to run the economy of the city, so new branding needs to be created for the welfare of society. The research seeks to examine and describe how new identities in the tourism sector in the city of Bitung through hexagonal Anholt. Methods research usesing case studies with a qualitative approach and interpretive paradigm. The establishment of Bitung city identity in the tourism sector through six hexagonal aspects is quite successfully for the tourism image of Bitung city to be better although it needs an increase in some aspects.